Mastering Stocks and Bonds Understanding How Asset Cross-Over Strategies will Improve Your Portfolio$1 (Bs Performance /s - Emons, Ben.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2015)
Despite popular belief, bond and stock investors are not opposites. Stock investors can apply bond strategies to safeguard returns. And bond investors can do better using a stock selection strategy designed to improve the portfolio's income distribution. This book will teach you to look at stocks through the lens of a bond buyer, and vice versa.
Keywords: History; Investment banking; Securities; Asia -- History; History; Asian History; Investments and Securities; Electronic books